The president sang Amazing grace - Mulford, Zoe, 1968- (Cameron kids, an imprint of Cameron+Company, 2019)
'Following the 2015 mass shooting that took nine lives in a historic Black church in Charleston, South Carolina, President Obama sang "Amazing grace" to a grieving congregation and nation. Inspired by the event, songwriter Zoe Mulford wrote a song called "The president sang amazing grace."' This picture book features the lyrics of this song and the paintings by filmmaker Jeff Scher, originally created for a short film for the song, performed by Joan Baez."--Front book flap.